The Effect of Egg Weight on Fertility, Hatchability, and Hatching Weight in Ducks: A Quantitative Observational Study - Aldiyanti, Amani; Rizkuna, Akhmat; 'Izzati, Farah Diba; Mualim, Mirna (Universitas Veteran Bangun Nusantara, 2026)
Egg weight is one of the physical characteristics often associated with reproductive performance in ducks, particularly fertility, hatchability, and hatching weight. This study aimed to evaluate the effect of egg weight on fertility, hatchability, and Day Old Duck (DOD) weight. A quantitative approach with an analytical observational design was applied to 100 duck eggs incubated under standard temperature and humidity conditions using an incubator. Parameters observed included egg weight, fertility (candling), hatchability, and DOD weight, which were analyzed using simple linear regression. The results showed that egg weight did not significantly affect fertility or hatchability. However, egg weight had a significant effect on DOD weight, indicating that heavier eggs provide greater nutrient reserves for embryonic development. In conclusion, egg weight is not a primary determinant of fertility and hatchability but plays an important role in determining the hatching weight of ducklings.